Foreign direct investment as a factor of growth: The experience of European Union countries - Kovačević Radovan (Međunarodni Problemi)
The empirical literature on the growth impact of foreign direct investment (FDI) suggests a strong positive relationship between the two. Yet, the lack of evidence of a clear causality from FDI to growth impedes our ability to firmly conclude that FDI inflows are a driver and not just a consequence of higher economic growth. Just as a higher return on investment typically attracts more fixed investment, it should be no surprise that it also attracts more foreign investors. Having said that, we need to acknowledge that the difficulty of finding unambiguous evidence of causality from FDI to growth does not refute the notion that such a relationship nevertheless exists. As the growth literature suggests, many different factors combine to create an environment conducive to higher economic growth. Proper policies and institutions have been found to be particularly important over longer periods of time. In this context, we need to view FDI from a broader perspective than its direct and immediate impact on growth itself. Could it not be the case, for example, that foreign investors are more demanding than indigenous firms as regards a stable and favourable policy environment, good infrastructure and an appropriate human capital stock? If governments introduce policies and create institutions with the purpose of attracting FDI, they may create an environment more generally favourable to growth even though some of this growth is not the result of FDI per se. The evidence is stronger that FDI has been boosting growth directly in Central and Eastern European countries (CEE) than in the 15 countries of the European Union (EU-15). The reason, as we have argued, is that while these countries needed to bridge the technology gap to the more advanced countries, they nevertheless met some key conditions - especially in terms of human capital - which helped them bridge this gap more quickly with the help of FDI. In addition, the sheer magnitude of net FDI inflows helped sustain a higher level of domestic investment than would have been possible on the basis of domestic saving and debt-creating capital inflows alone. While FDI is expected to continue to contribute to economic growth in the CEE countries that have joined the EU, it is less clear whether the economic gains from FDI will be as high as during the transition from plan to market. The more the new EU members come to resemble EU-15 countries in terms of inward FDI stocks as a share of GDP, productivity, efficiency and level of technology, the less likely it is that FDI will have a positive influence on economic growth beyond what is observed in more advanced market economies. That said, FDI and the associated activities of transnational corporations will undoubtedly remain an important welfare-enhancing force - both inside and outside an enlarged European Union.